Pristiophorus lanae sp. nov., a new sawshark species from the Western North Pacific, with comments on the genus Pristiophorus Müller & Henle, 1837 (Chondrichthyes: Pristiophoridae) - Ebert, David A.; Wilms, Hana A. (Zootaxa, 2013)
A new species of sawshark, Pristiophorus lanae sp. nov., is described from off the Philippine Islands. The new species is the second member of the genus Pristiophorus described from the western North Pacific and can be separated from its closest geographic congener, P. japonicus, by having fewer rostral teeth in front of rostral barbels (17–26 versus 25–32), mouth at corners extending forward to below the rear margin of the eye versus extending below the rear one-third of eye margin, a greater mouth width at 6.9–7.8 times into pre-oral length (versus 5.8–6.9), eye length into head length (15.6–15.9 versus 9.8–13.2), mouth width into head length 9.0–10.0 versus 7.4–8.5 times, head width at nostrils 5.2–6.1 times into pre-orbital length versus 3.9–4.9 times, shorter prebarbel length (from snout tip to barbel) of 50.7–54.5% of preoral length versus 53.6–59.2%, a snout angle of 10.6–13.0° versus 12.4°–14.6°, and lateral trunk denticles with flat crowns that are imbricated versus erect crowns that are not imbricated. The number of monospondylous vertebrae is slightly lower in P. lanae (43–48) versus P. japonicus (51–52). The genus is reviewed, with a revised key to its species presented.